Toward climate resilient land-use planning: Indicators for adaptation and mitigation - Yinuo Zhou; Shahryar Sarabi; Qi Han (Environmental and Sustainability Indicators)
As climate and land-use pressures intensify, Climate resilient land-use (CRLU) planning is becoming increasingly essential. This study conducts a scoping review of 115 studies to examine how adaptation and mitigation are addressed in CRLU planning, focusing on the indicators used to measure these goals. The review analyzes indicators across agriculture, forestry, and urban planning sectors, revealing an imbalance emphasizing climate mitigation over adaptation indicators. It also distinguishes urban and rural contexts, highlighting the need for region-specific indicators. Synergies and trade-offs between adaptation and mitigation indicators are then discussed to inform integrated planning and avoid unintended negative consequences. The review also evaluates CRLU modeling approaches, from pattern-based to process-based, and finds that their effectiveness depends on selecting indicators closely aligned with planning objectives. A conceptual framework is finally proposed to guide the selection of targeted, context-sensitive, comprehensive indicators, supporting more effective CRLU planning.